A systematic review of parasites and micropredators of non-avian reptiles (Reptilia=Sauropsida) in Chile - San-Martín-Órdenes, Julio; Muñoz-Leal, Sebastián; Garín, Carlos F.; González-Acuña, Daniel (Zootaxa, 2019)
Knowledge about the identity of parasites in vertebrates is relevant because of their influence on ecological processes and health of their hosts. This is particularly important for groups of animals currently facing conservation issues, such as reptiles. The diversity of species and supra-specific taxa of microparasites and macroparasites (such as helminths and arthropods) present in non-avian reptiles in Chile was analyzed through a systematic review. A total of 49 scientific documents (thesis projects, abstracts in congresses, book chapters and peer-reviewed articles) concerning parasites, taxonomic descriptions and parasite ecology were included in this review. The suborder Iguania was among the most studied group with 35 native species recognized as hosts of parasites and 39 species of parasites reported up to the category of species or genus. Liolaemus tenuis was the species with the most taxa of recorded parasites (11 taxa, and only three to species level), but Liolaemus chillanensis had the highest number of identified species of parasites. In addition, only one native species of Serpentes, one of Gymnophthalmoidea, and two of Gekkota, as well as some reports of exotic species, were recorded as hosts. Among parasites, Trombidiformes was the richest order with 10 species from the superfamily Pterygosomatoidea and 16 species from Trombiculoidea. Current knowledge about the richness of helminths is very limited and there were only a few records of microparasites. In general, there is an urgent need for the development of collaborative works between specialists in reptile taxonomy and epidemiology in parasitology destined to evaluate the consequences that reptiles and their parasites will suffer due to the ongoing processes of habitat loss, climate change and the still present taxonomic issues of the native reptiles.